Penggunaan model pembelajaran talking stick berbantuan media kuis interaktif quizizz untuk meningkatkan pemahaman konsep sumber energi peserta didik - Amelia, Febrisha Arya; Matsuri, Matsuri; Saputri, Dwi Yuniasih (Universitas Sebelas Maret, 2023)
This classroom action research explains the application of learning using the talking stick learning model assisted by Quizizz interactive quiz media with the aim of increasing understanding of the concept of energy source material in grade IV students at SD Negeri Gawan 1, Gawan Village, Tanon District, Sragen Regency. This class action research is based on a mixed qualitative and quantitative research design because in reading the problem descriptive and quantitative data in the form of numbers. The subjects in this study are grade IV teachers as collaborators and grade IV students of SD Negeri 1 Gawan for the 2022/2023 school year. Data in this study were obtained through interviews, observations, documentation, and tests in the form of pretest and posttest. The validity test technique in this study uses data source triangulation and method triangulation. Data in this study were obtained through interviews, observations, documentation, and tests in the form of pretest and posttest. The validity test technique in this study uses data source triangulation and method triangulation. This research was carried out for three cycles with four stages each, namely planning, implementation, observation, and reflection. The steps for implementing Quizizz's media-assisted talking stick model use the 11 steps described in chapter 2. Based on the implementation of learning using the talking stick learning model assisted by interactive quiz media, Quizizz can improve the understanding of the concept of energy source material in grade IV students in three cycles. The percentage of completeness increased in each cycle, namely cycle 1 by 22.22%, in cycle 2 by 55.56%, and cycle 3 by 88.89%.